Functional Properties of Rapeseed Honey Enriched with Lyophilized Fruits - Aleksandar Marić; Marijana Sakač; Pavle Jovanov; Branislava Đermanović; Nemanja Teslić; Dragana Plavšić; Dimitar Jakimov (Agriculture, 2024)
This study evaluates the physicochemical characteristics, antioxidant, antibacterial, and antiproliferative properties of rapeseed honey collected from Vojvodina, Serbia, as well as rapeseed honey-based products enriched with 10% fruit lyophilizate, including sour cherry (Prunus cerasus), strawberry (Fragaria), blueberry (Vaccinium myrtillus), raspberry (Rubus idaeus), blackberry (Rubus fruticosus), orange (Citrus sinensis), and pineapple (Ananas comosus). Honey-based products with lyophilizates were developed to enhance the relatively limited therapeutic potential of rapeseed honey by incorporating fruit lyophilizates known to possess bioactive compounds. The moisture content, pH, electrical conductivity, free acidity, hydroxymethylfurfural (HMF), and mineral composition were analyzed. Sour cherry-enriched honey exhibited the highest total phenolic content (TPC = 102 ± 0.18 mg GAE/100 g), while blueberry-enriched honey had the highest total flavonoid content (TFC = 34.9 ± 0.89 mg CAE/100 g) and total anthocyanin content (TAC = 299 ± 3.14 mg EC/100 g), with the greatest relative scavenging capacity (81.0 ± 0.46% of DPPH inhibition). Polyphenol profiling identified phenolic acids and flavonoids, with raspberry-enriched honey showing the highest total polyphenol content (47.0 ± 0.98 mg/kg) due to its high ellagic acid content (38.4 ± 1.11 mg/kg). All honey-based products demonstrated moderate antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis. Significant antiproliferative effects against breast (MCF-7), cervix (HeLa), and colon (HT-29) cancer cell lines were observed, particularly in pineapple and blueberry-enriched honey, with IC50 values as 9.04 ± 0.16 mg/mL and 9.95 ± 0.24 mg/mL for MCF-7 cells, respectively. Based on all the obtained results, it can be concluded that the enrichment of rapeseed honey with fruit lyophilizates at a 10% level contributed to an increase in the antioxidant, antibacterial, and antiproliferative properties of rapeseed honey.